Performance evaluation of two-worker operations in a worker-to-cell order assorting system. (July 2020) - Hong, Soondo
Highlights: Introduce a manual assorting operation in a worker-to-cell order assorting system with Put-To-Light technology. Evaluate two worker-assignment policies: a dedicated-assignment policy and a shared-assignment policy. Develop closed-form expressions of worker process time and system flow time including waiting time and blocking delay. Compare two policies using worker-centric measure (worker process time) and system-centric measure (system flow time).. Abstract: This paper studies an order assorting system (OAS) composed of multiple-parallel order assorting aisles (OAAs) in a retailer's order fulfillment center. We evaluate two worker-assignment policies for a worker-to-part OAA: a dedicated-assignment policy and a shared-assignment policy. Our analytical models evaluate the mean value and variance of worker process time including assorting time, walk time, empty walk time, and blocking time when single-line products arrive randomly. From the worker process time, we identify the system flow time of product lines per each worker-assignment policy using G / G /1 and G / G /2 queuing models. We find that the shared-assignment policy performs better compared to the dedicated-assignment policy in spite of workers' productivity losses incurred by blocking delays over high sort probability, slow walk speed, and high magnitude and variations of inter-arrival times. At the worker-centric break-even point of worker process time, where worker process time suggests selecting either policy, system flow time always suggests selecting the shared-assignment policy.